Reactualization of the Serat Menak Lare in the Wangsalan Sindhenan Srambahan - ., Siswati (Sutasoma : Jurnal Sastra Jawa, 2025)
This study discusses the process of making Wangsalan Sindhenan Srambahan, which is based on the Menak story. Menak's story is one of the most popular stories in Java, and it has been adapted into wayang and dance performances. Of the many performances related to menak stories, the cakepan wangsalan sindhenan has not been found, which is an essential element when accompanying menak performances. Research about Wangsalan menak stories is expected to contribute to menak story performances. This qualitative research uses descriptive analysis methods and the transfer of vehicles method. Data were collected through literature studies and paramasastra processing. The data analysis technique used is the reciprocity of data from document studies with Paramasastra. The results of this study are Wangsalan Srambahan from Menak stories, which can be used as a reference when accompanying Menak-themed performances.